ENGINEERING MANAGEMENT OF GRAIN HARVESTER FAILURE MANAGEMENT UNDER TECHNOLOGY OF MAINTENANCE TECHNOLOGY - Kuzmich, I. M.; Rogovskii, I. L. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2022)
The article discusses the feasibility of applying the normative complex of engineering management for adaptive maintenance technology in the storage of combine harvesters. The basis of experimental research is the working scientific hypothesis that the efficiency of machine use of combine harvesters largely depends on its reliability, in particular on the indicators of failure directly in the harvest process. When harvesting grain crops, it is necessary to ensure the working condition of combines during the normative agro-technical period. Therefore, the main characteristic feature of combine harvesters is characterized by reliability. It is assumed that the failure of combine harvesters for technical and technological reasons leads to downtime of the combines and, as a consequence, to the loss of part of the grain harvest. If the established normative agro-technical term of grain harvesting is exceeded, the specific losses of grain are 0.004…0.006 % for one hour of downtime. Analysis of statistical data on the technical condition of facilities on the basis of operational observations revealed possible patterns and causes of failures. The analysis of results of experimental researches with establishment of numerical values of indicators of failure of grain harvesters is carried out, namely, average time on the first failure, average time on failure, average number of failures, average time of elimination of failure, coefficient of variation of failures. Graphic interpretation of the dependence of failure indicators of combine harvesters is presented, namely, the density of failure of combines, the total number of failures in the process of combines, the total readiness factor of combine harvesters. The existence of the influence of the change in the average operating time on the failure in the process of operation of combines on the indicators of failure of the combine has been confirmed. The considered approach with a similar analysis allows to reasonably put forward requirements to the characteristics of maintenance technologies during storage of combine harvesters.